Oral candidosis in relation to oral immunity. (9th October 2013) - Feller, L.; Khammissa, R. A. G.; Chandran, R.; Altini, M.; Lemmer, J.
<x xml:space="preserve">Abstract</x> Symptomatic oral infection with Candida albicans is characterized by invasion of the oral epithelium by virulent hyphae that cause tissue damage releasing the inflammatory mediators that initiate and sustain local inflammation. Candida albicans triggers pattern‐recognition receptors of keratinocytes, macrophages, monocytes and dendritic cells, stimulating the production of IL‐1β, IL‐6 and IL‐23. These cytokines induce the differentiation of Th17 cells and the generation of IL‐17‐ and/or IL‐22‐mediated antifungal protective immuno‐inflammatory responses in infected mucosa. Some immune cells including NKT cells, γδ T cells and lymphoid cells that are innate to the oral mucosa have the capacity to produce large quantities of IL‐17 in response to C. albicans, sufficient to mediate effective protective immunity against C. albicans. On the other hand, molecular structures of commensal C. albicans blastoconidia, although detected by pattern‐recognition receptors, are avirulent, do not invade the oral epithelium, do not elicit inflammatory responses in a healthy host, but induce regulatory immune responses that maintain tissue tolerance to the commensal fungi. The type, specificity and sensitivity of the protective immune response towards C. albicans is determined by the outcome of the integrated interactions between the intracellular signalling pathways of specific combinations of activated pattern‐recognition receptors (TLR2, TLR4, Dectin‐1 and Dectin‐2). IL‐17‐mediated protective immune response is essential for oral mucosal immunity to C. albicans infection.